Analysis of Organizational Culture and Communication on Employee Job Satisfaction in the Directorate General of Taxes - Bangun Wijanarko; Zulkifli Rangkuti; Nurwulan Kusuma Devi (Dinasti Publisher, 2026)
The purpose of this study is as follows to determine the influence of Organizational Culture on Employee Job Satisfaction, to determine the influence of Communication on Employee Job Satisfaction, to determine the influence of Organizational Culture and Communication on Employee Job Satisfaction in the Directorate General of Taxes . the calculated t value for the Organizational Culture variable (X1) is 4.067 , while the t table value for n = 40 is 2.021 . So t count> t table or 4.067> 2.021 , then H0 is rejected and Ha is accepted , it can be stated that Organizational Culture ( X1 ) has a significant effect on Job Satisfaction ( Y), the results of the t test the calculated t value for the Communication variable ( X2 ) is 4.194 .... 194 > 2.021 , then H0 is rejected and Ha is accepted, it can be concluded that partially the Communication variable (X2 ) has an effect on Job Satisfaction (Y). The R Square value is 0.678 . This shows that 67.8 % of Organizational Culture (X1 ) and communication (X2 ) together have an effect on Job Satisfaction (Y), while the remaining 32.2% is influenced by other factors not examined in this study